Sifat Kuantitatif Aktivitas NitratReduktase Padi (Oryza Sativa L.) - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2003)
. ABSTRACT All of the research activities were carried out in Greenhouse and Biochemistry Laboratory at Faculty of Biology, Gadjah Mada University Yogyakarta. In this research, four rice cultivations which each represents four different product capacities were used. These four cultivations are outbreeding results of each parental which is also the result of outbreeding. The measuring of the nitrate reductase activities is carried out to 40 individuals of each cultivation having the incubation time treatment (T) 30, 60, 120 and 360 minutes and substrate treatment of 0, 0,05, 0,1, and 0,2 M. The results revealed that from the ANR measurement result of those four substrate treatments, it is only on the substrate treatment [0] M that can be divided into class intervals having distribution and frequency dispersions, and having one top as the quantitative genetic characteristic. The phenotype shown by the quantitative genetic characteristics seems to have level forming a varied spectrum in one genotype class based on the intensity of the characteristic expression it self. Those four cultivations showed that the difference of the distribution and frequency dispersions indicates that those four cultivations have the ANR quantitative characteristics, which is different from the different genotype. Keywords : nitrate reductase, quantitative, frequency distributions and dispersions, activity, phenotype, genotype